2013
DOI: 10.7482/0003-9438-56-084
|View full text |Cite
|
Sign up to set email alerts
|

The effect of <i>Myrtus communis</i> oil extract on growth performance, serum biochemistry and humoral immune responses in broiler chicks fed diet containing aflatoxin B1

Abstract: Abstract. A study was conducted to investigate the capability of Myrtus communis essential oil (MCE) in counteracting the deleterious effects of aflatoxin B1 (AFB1) on growth performance, serum biochemistry and humoral immune responses in broiler chickens. In a completely randomized design, 300 day-old male chicks were assigned to four treatments with five replicates of 15 birds for 42 days. Chickens, up to day 7 of age, were fed the same diet and then, they were fed the experimental diets. The dietary treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…We observed that dietary supplementation of 120 and 240 mg/kg EO significantly increased the serum NDV antibody titers compared with the basal diet or diet with 60 mg/kg EO in the challenged birds. This was consistent with previous studies, which demonstrated that dietary supplementation of EO enhanced the specific immune responses in broilers and laying hens [ 14 , 46 , 47 ]. As the most abundant immunoglobulin isotype in mucosal secretions, sIgA is the fundamental effector to mucosal immunity.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that dietary supplementation of 120 and 240 mg/kg EO significantly increased the serum NDV antibody titers compared with the basal diet or diet with 60 mg/kg EO in the challenged birds. This was consistent with previous studies, which demonstrated that dietary supplementation of EO enhanced the specific immune responses in broilers and laying hens [ 14 , 46 , 47 ]. As the most abundant immunoglobulin isotype in mucosal secretions, sIgA is the fundamental effector to mucosal immunity.…”
Section: Discussionsupporting
confidence: 93%
“…Mycosorbents are able to bind aflatoxin molecules in the gastrointestinal tract and thus, to reduce their absorption by domestic fowl. The results agree with data from other studies with mycosorbents as clinoptiolite (Oguz et al, 2003), hydrated calcium aluminosilicate (HSCAS), sodium bentonite, montmorillonite (Ologhobo et al, 2015), essential oils (Saei et al, 2013), antioxidants (resveratrol) (Sridhar et al, 2015) and probiotics (Zuo et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Reduced feed utilisation is also a result from the decreased activity of a number of enzymes involved in carbohydrate, proteins, nucleic acids conversion, to reduced intake or nutritional deficiency (Makinia, 2014). On the other hand, the lower feed intake is attributed to increased blood ammonia concentrations following reduced glomerular filtration rate (Saei et al, 2013). The lower weight gain is due to reduced protein synthesis rate, impaired lipogenesis, reduced protein and lipid utilisation from feeds, enhanced faecal excretion of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, especially on the 33rd day of the study, it was determined that the body weight value of the quails in the M and MLPS groups was significantly lower than the control and LPS group quails (P<0.05). However, it was reported that the addition of murt oil to Japanese quail feed (1000 mg/kg/day, Biricik et al 2012) and broiler feed (500 mg/kg, Sadeghi et al 2013;Goudarzi et al 2016) had a positive effect as a potential growth promoter. Animal performance characteristics and the dose difference of the herbal antioxidant added to the basal diet can be expressed as an important reason for the differences in the study results.…”
Section: Discussionmentioning
confidence: 99%